Role of Polysaccharides in Complex Mixtures with Soy Protein Hydrolysate on Foaming Properties Studied by Response Surface Methodology - Martínez, Karina Dafne (2013)
The complex mixture studied, a hydrolyzed soy protein (HSP), κ-carrageenan (κC), and an hydroxypropyl methylcellulose (HPMC), could be used as a foaming agent under refrigeration or heating conditions because of the presence of one polysaccharide (HPMC) that gels on heating and another (κC) that gels on cooling. The objective of this work was to study the role of these polysaccharides on foaming properties by whipping methods at heating conditions. For this purpose, response surface methodology was used to optimize the mixed product in foamed food systems. The obtained results showed that the combination of E4M, κC, and HSP is an adequate strategy to generate good foam capacity and stability at heating conditions. The huge stability increase of foams at heating conditions was ascribed to combined effect of polysaccharides: gelling property of E4M and the viscozieng character imparted by κC to continuous phase of foaming.